Otoritas Alkitab: Tinjauan Teologi Sistematis Pemikiran Luther Menjawab Skeptisisme Teologi Kontemporer Tentang Alkitab Sebagai Firman Allah - Rinaldi Girsang; Insan Sinurat; Sitompul, Victor Golan (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
The purpose of writing this article is to explore Martin Luther's view of the Bible as the authoritative Word of God as a critical answer to the doubts of contemporary groups. This article refers to the results of Luther's thoughts in documents and systematic theology classroom notes. The meaning of what and how the Bible is for Luther is the most fundamental thing that is intertwined with history, travel, and church growth. By using library research methods, the author finds Luther's critical thoughts regarding the Bible his criticism of the Roman Catholic Church, to the doubts of contemporary groups regarding the Bible which is understood as God's Word in all centuries throughout life.